Prolactinoma presenting with secondary amenorrhoea in a young girl - Halima Hana AK,; Leelavathi Muthupalaniappen,; Katiman E,; Aziz NA, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Prolactinoma is the most common secreting pituitary adenoma. It has different clinical presentation in men and women which varies with age. Young women present with menstrual problems, infertility and galactorrhoea, whilst older women and men may present with loss of libido, visual disturbances and in late cases, with osteoporosis. In approaching a young woman with secondary amenorrhoea, other causes such as pregnancy, functional hypothalamic amenorrhea, pituitary adenoma, Polycystic Ovarian Syndrome (PCOS) or primary ovarian insufficiency should be ruled out. Prolactinoma can be confirmed in the presence of high serum prolactin level and adenoma on pituitary gland magnetic resonance imaging (MRI). Dopaminergic agonist, cabergoline is efficacious in restoring gonadal and sexual functions by normalising prolactin levels. We presented a case report on an 18-year-old girl who presented with secondary amenorrhoea for six months. On further evaluation she was noted to have galactorrhoea with substantially high prolactin level of 466.9 ng/mL (normal range: 4.0- 23) and the MRI showed a pituitary tumour measuring 1.2 x 1.1 x 1.4 cm. A diagnosis of macroprolactinoma was made and she was managed with cabergoline with gradual dose increment. At 6 months of treatment, her menstrual cycle and serum prolactin had normalised. A repeat MRI pituitary one year later showed reduction in tumour size.